KOMERSIALISASI PENDIDIKAN TINGGI DI INDONESIA - Wahyudi, Imam (Tawazun: Jurnal Pendidikan Islam, 2018)
Educational orientation confounded by priority serve global competition rather than maintain local harmony. Formal institutions has been held hostage by the interests of industrial capitalism. Character of capitalism is seen from the emergence of the spirit of the ideology of competition which requires all parties to compete obtain educational services to all kinds of ways. Legalizing liberal view to obtain a quality education has to spend a lot. Just like an item that can be freely traded in the market, as if education can be ordered according to the ability of the economic capital of each individual. In Islam, the purpose of education is to form the personality of Islam (syakh-shiyah Islamiyah) learners and provided him with a variety of science and knowledge relating to life. The state must ensure education for all citizens with cheap / free. Thing that distinguishes between Islam and neoliberalism, in Islamic education funding entirely the responsibility of the state. Education will be implemented properly if it is supported by adequate funding because the quality of education can not be separated from the availability of funds. The source of these funds from endowments, zakat, alms, grants, and other funding sources are kosher and non-binding.